2019
DOI: 10.3390/cancers11081188
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Cancer: Clinical Picture of the Last Two Decades at a Single Oncology Referral Centre and Novel Therapeutic Options

Abstract: Anaplastic thyroid cancer (ATC) is a rare tumour but also one of the most lethal malignancies. Therapeutic modalities have usually been limited, but clinical trials with new drugs are now being implemented. The aims of this study were to analyse the clinical presentation, therapeutic modalities and independent prognostic factors for survival. We also reviewed the most recent literature on novel ATC therapies. We performed a retrospective analysis of 79 patients diagnosed between 2000 and 2018. Variables with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Importantly, more than 40% of all ATC cases occur in advanced stages, which means that symptoms of local compression with dyspnea and dysphagia and/or distant metastases are present [ 1 , 5 , 8 , 13 , 14 , 66 ]. These cases correspond to the unresectable stage IVB or stage IVC, in which, usually, no surgery or only an incomplete resection (R2) is possible [ 2 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, more than 40% of all ATC cases occur in advanced stages, which means that symptoms of local compression with dyspnea and dysphagia and/or distant metastases are present [ 1 , 5 , 8 , 13 , 14 , 66 ]. These cases correspond to the unresectable stage IVB or stage IVC, in which, usually, no surgery or only an incomplete resection (R2) is possible [ 2 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cases correspond to the unresectable stage IVB or stage IVC, in which, usually, no surgery or only an incomplete resection (R2) is possible [ 2 , 5 , 7 ]. In this situation, definitive chemoradiotherapy may provide local control and symptomatic relief [ 6 , 7 , 8 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that overexpression of the epidermalgrowth factor receptor (EGFR) is strongly associated with tumorprogression, migration, and invasion. EGFR is common in ATCpatients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Simões-Pereira et al analyzed the clinical presentation, therapeutic modalities and outcomes, as well as the prognostic factors influencing disease specific survival (DSS), in a homogenous population of ATC followed at a single institution. They showed that most of the patients join reference centers at advanced stages of disease and multimodality treatment may offer the best chances for prolonging survival [ 25 ]. Ravi et al performed whole exome sequencing and the RNA-sequencing of fourteen cases of ATC to delineate copy number changes, fusion gene events, and somatic mutations.…”
mentioning
confidence: 99%